2014
DOI: 10.1095/biolreprod.114.119057
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Contributes to Luteolysis by Binding to Beta 1 Integrin in the Bovine Corpus Luteum1

Abstract: Luteolysis is characterized by a reduction in progesterone (P4) production and tissue degeneration in the corpus luteum (CL). One of major events during luteolysis is luteal cell death. Galectin-3, a ubiquitously expressed protein involved in many cellular processes, serves as an antiapoptotic and/or proapoptotic factor in various cell types. Although galectin-3 is detected in the bovine CL, its role remains unclear. The expression of galectin-3 in the bovine CL was higher at the regressed stage than at the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…Galectin-3 participates in the ECM-cell adhesion process, and the association between galectin-3 and ECM proteins, particularly laminin and fibronectin, is essential for leucocyte movement. Furthermore, the interaction of galectin-3 with fibronectin is unique for the macrophage migratory process (23), indicating that galectin-3 may guide monocyte-derived macrophages to transmigrate across the endothelium and reach the arterial media, via its ECM binding ability. Previous studies have demonstrated that galectin-3 has no impact on the expression of adhesion molecules, such as selectin, ICAM, VCAM and very late antigen-4, indicating that galectin-3 is not an inflammatory modulator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galectin-3 participates in the ECM-cell adhesion process, and the association between galectin-3 and ECM proteins, particularly laminin and fibronectin, is essential for leucocyte movement. Furthermore, the interaction of galectin-3 with fibronectin is unique for the macrophage migratory process (23), indicating that galectin-3 may guide monocyte-derived macrophages to transmigrate across the endothelium and reach the arterial media, via its ECM binding ability. Previous studies have demonstrated that galectin-3 has no impact on the expression of adhesion molecules, such as selectin, ICAM, VCAM and very late antigen-4, indicating that galectin-3 is not an inflammatory modulator.…”
Section: Discussionmentioning
confidence: 99%
“…VCAM-1 may mediate rolling-type adhesion and firm adhesion, depending on the avidity status of α4β1-integrin (25). It has been demonstrated that galectin-3 is capable of associating with β1 integrin, via its carbohydrate recognition domain, in a lactose-dependent manner (23). The binding of galectin-3 with α4β1 integrin may further modulate its receptor state and alter its affinity to VCAM-1; therefore, galectin-3 may be indirectly involved in α4β1-integrin-VCAM-1 dependent rolling and adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…The stromal cells exhibited a significant 177-fold increase of SLC15A3 while glandular epithelial cells had a 36-fold increase [181]. Data from the current study show the up-regulation of SLC15A3 in the epithelial and fibroblast cells due to IFNT (logFC 6.29 and 7.06, respectively; protein from humans and an unidentified mammal in vitro to elicit a response on cultured bovine luteal cells [118]. However, we conclude that recombinant mouse LGALS3 protein did not elicit a cellular response in the bovine cells.…”
Section: Discussionmentioning
confidence: 51%
“…Specifically, in the nonpregnant bovine uterus, LGALS3 has been localized via IHC in epithelial cells as well as macrophages located in the submucosa but absent in endometrial glands [117]. In the bovine CL, LGALS3 expression was elevated at the regressed state in comparison to all other luteal stages and was localized on steroidogenic cells in the CL [118].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation